Tanggung Jawab Sosial Universitas dan Tata Kelola Universitas Terhadap Citra UIN Syarif Hidayatullah Jakarta - A. Atiqah (Akuntabilitas, 2019)
This research aims to examine that University Social Responsibility (USR) and Good University Governance (GUG) influence toward image of UIN Syarif Hidayatullah Jakarta. Indicator of USR include economic responsibilities, legal responsibilities, ethical responsibilities and philanthrophic responsibilities. Indicator of GUG include transparation, accountability, responsibility, independency, fairness and participation. Indicator of Image include Reputation, Personality, ethical/value and corporate identity. Sample of this research include civitas academic of UIN Syarif Hidayatullah Jakarta include student, lecturer and officer. Technic analysis data use multiple linear regression. Results of this research as partial provide evidence that University Social Responsibility influence toward image of UIN Syarif Hidayatullah Jakarta, and Good University Governance influence toward image of UIN Syarif Hidayatullah Jakarta.